The academic/practitioner divide in marketing - myth or reality? - Brennan, Ross (Marketing Intelligence & Planning., 2004)
In marketing, as in other areas of management studies, there is a feeling abroad that lines of communication need to be improved between those who work largely in the academic sphere and the practitioner community. Introduces the papers presented in this special issue, which explore the nature of the "academic-practitioner divide", investigate the reasons for it and the barriers to communication that exist, and put forward ideas for improving the effectiveness of academic-practitioner collaboration. However, members of the academic community should carefully avoid a headlong and uncritical rus.